The relationship between the President of the Republic of Kosovo and the Assembly in general and in particular in the time period 2011-2016 - Susuri, Driola (Technium Social Sciences Journal, 2022)
The Constitution of the Republic of Kosovo in its basic provisions has defined the form of government and separation of state powers, as a fundamental principle of democracy, where the President of the Republic of Kosovo is not part of any of the state powers, but the constitutional powers he exercises affect that he has connections with all state powers. This paper addresses the relation of the President of the Republic of Kosovo with the legislative power, including the exercise of some of his constitutional powers, namely the convening of the constitutive session of the Assembly, the dissolution of the Assembly and the annual speech of the President in the Assembly of the Republic of Kosovo. The above-mentioned competencies, in addition to the theoretical aspect, are also analyzed in the practical aspect when these constitutional competencies of the President were materialized by President Jahjaga during the mandate 2011-2016. Also, the political stalemate and the actions taken by the President, Mrs. Atifete Jahjaga for his overcoming, criticisms and recommendations of the European Commission in the Progress Reports regarding the political stalemate in the country. since the declaration of Kosovo as an independent state in 2008, it has managed to complete a full constitutional mandate, five years, unlike its predecessors and successors until 2019. Therefore, this paper aims to elaborate the exercise of some constitutional powers and the practice of one of the most important constitutional institutions in the Republic of Kosovo, that of the President of the Republic of Kosovo.